(untitled) (CAHIERS MAGELLANES-NS, 2024)
Stress and coping are intertwined processes that influence how individuals respond to challenging situations. Stress can arise from various sources such as work pressures, relationship issues, health concerns, triggering emotional, physical, and cognitive reactions. Coping mechanisms are strategies people use to manage stress and reduce its negative effects. Critical care nurses play a pivotal role in the healthcare industry, providing essential care to patients in intensive care units (ICUs) and other critical care settings. Beyond technical skills, critical care nurses offer compassionate support to patients and their families, navigating the emotional challenges of intensive care. In other hand, critical care nurses face significant stress due to the demanding nature of their work and the high stakes involved in caring for critically ill patients. These healthcare professionals often deal with intense situations, such as life-threatening emergencies, complex medical conditions, and the emotional strain of supporting patients and their families through difficult times. The stressors can include long work hours, heavy workload, rapid decision-making, and exposure to suffering and death. Chronic stress can significantly impact their well-being, leading to burnout, decreased job satisfaction, and potentially compromising patient care. By assessing stress levels, healthcare institutions can identify early signs of burnout and intervene with appropriate support measures. This proactive approach not only helps in retaining experienced nurses but also ensures the delivery of high-quality patient care. Thus, the present study is to aim to assess the stress and coping among critical care nurses and association of stress with their demographic variables. The study was conducted in selected hospital of Aurangabad city. Non probability convenient sampling technique was used and obtained 90 critical care nurses. The study result shows that high level of stress was prevalent among critical care nurses 73.33%, 26.67% nurses experienced moderate stress. Level of coping was low among 85.56% nurses and 14.44% nurses had medium coping.